Intestinal lactase, sucrase and alkaline phosphatase in relation to age, sex and site of intestinal biopsy in 477 Irish subjects. Issue 1 (January 1983) - Keane, R; O'Grady, J G; Sheil, J; Stevens, F M; Egan-Mitchell, B; McNicholl, B; McCarthy, C F; Fottrell, P F
Abstract : Small intestinal lactase, sucrase and alkaline phosphatase activities were measured in histologically normal peroral intestinal biopsies from 477 individuals. Enzyme activities varied with age, sex, site of biopsy, and were lowest in post-weaning children and highest in young adults. Lactase activity does not decrease with advancing age.